LESSONS LEARNED FROM THE 12 STEPS LISTED BY ALCOHOLICS ANONYMOUS REHABILITATION PROGRAM - Tanu Priya (International Journal of Multidisciplinary Research and Studies, 2021)
Alcohol, which is available in liquid form, is a drug that is both sedative and intoxicating. In its unaltered form, it may be ignited by heat or flame. It is good in low amounts due to the fact that it activates cells and hormones, but it is dangerous in high levels since it is beyond what the human body is able to digest at one time. In the most severe cases, it may possibly lead to death or a coma. People in every part of the world partake in the use of alcoholic beverages. Alcoholism is a popular form of self-medication and an improvement approach for those who suffer from mental disease and sadness (Gunderson 1997). Between the years 1992 and 2012, India had a tremendous rise of over 55% in the per capita rate of the proportion of people who were alcoholics.